2017
DOI: 10.1016/j.surfcoat.2016.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation study of electrodeposited Ag thin coating: An inverse calculation of anisotropic elastic-plastic properties

Abstract: A new inverse method was proposed to calculate the anisotropic elastic-plastic properties (flow stress) of electrodeposited Ag thin coating utilizing nanoindentation tests, previously reported inverse method for isotropic materials and three-dimensional (3-D) finite element analyses (FEA). Indentation depth was ~4% of coating thickness (~10 μm) to avoid substrate effect and different indentation responses were observed in the longitudinal (L) and the transverse (T) directions. The estimated elastic-plastic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 61 publications
0
21
1
1
Order By: Relevance
“…3, it can be seen that the results of the 10 measurements on the original coating, especially during loading, were more homogenous than those on the thermally aged coating. It has been reported that differences in surface roughness lead to dispersion of loading curves [37]. However, in this study, the original and thermally aged coatings had similar surface roughness values, and so, the large dispersion of the loaddisplacement curves for the thermally aged coating was caused by other factors.…”
Section: Study Of Mechanical Propertiescontrasting
confidence: 50%
“…3, it can be seen that the results of the 10 measurements on the original coating, especially during loading, were more homogenous than those on the thermally aged coating. It has been reported that differences in surface roughness lead to dispersion of loading curves [37]. However, in this study, the original and thermally aged coatings had similar surface roughness values, and so, the large dispersion of the loaddisplacement curves for the thermally aged coating was caused by other factors.…”
Section: Study Of Mechanical Propertiescontrasting
confidence: 50%
“…For example, the stiffness of a Cu thin film was observed to increase as the film thickness decreased due to the increase of <111> fiber texture component [21]. Similarly, the anisotropic elastic-plastic properties of the electrodeposited Ag thin coating were recognized by nanoindentation testing on the longitudinal and transverse directions of the coating surfaces [22]. It was reported, however, that the elastic modulus measured by a cantilever microbeam test was close to that in the parallel direction to the film surface [23].…”
Section: Discussionmentioning
confidence: 97%
“…Contohnya, nilai kekerasan dan modulus Young dapat diperoleh daripada beban maksimum dan permulaan cerun pembebanan seperti yang dicadangkan oleh Oliver dan Pharr (2004). Ujian pelekukan nano juga telah digunakan untuk menentukan modulus Young dan kekerasan filem nipis, perubahan mikrostruktur dan bahan pukal (Cheng et al 2017). Kajian oleh Chen et al (2015) telah menggunakan ujian pelekukan nano untuk mengkaji sifat mekanik struktur sambungan pateri, pateri pukal dan keadaan selepas pematerian.…”
Section: Pengenalanunclassified